2005
DOI: 10.1243/146441905x10041
|View full text |Cite
|
Sign up to set email alerts
|

Finite element analysis of the geometric stiffening effect. Part 1: A correction in the floating frame of reference formulation

Abstract: The fact that incorrect unstable solutions are obtained for linearly elastic models motivates the analytical study presented in this paper. The increase in the number of finite elements only leads to an increase in the critical speed. Crucial in the analysis presented in this paper is the fact that the mass matrix and the form of the elastic forces obtained using the absolute nodal coordinate formulation remain the same under orthogonal coordinate transformation. The absolute nodal coordinate formulation, in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 24 publications
5
26
0
Order By: Relevance
“…Special attention must be paid to Equation (27). As can be seen, the element is able to give the exact value provided by the linear theory of elastic beams.…”
Section: Improved Beam Elementmentioning
confidence: 99%
See 2 more Smart Citations
“…Special attention must be paid to Equation (27). As can be seen, the element is able to give the exact value provided by the linear theory of elastic beams.…”
Section: Improved Beam Elementmentioning
confidence: 99%
“…It has been extensively studied in the literature (see for example Refs. [27,28]). In this example, a flexible beam is subjected to a prescribed rotation around a perpendicular axis that passes through one of its ends.…”
Section: Numerical Examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of change of the manipulator rotation makes the effect of centrifugal stiffening terms more significant. While for most flexible robotic manipulators, the link axial and torsional vibration modes can be neglected, in solving rotating beam problems using the FFR formulation, an incorrect and unstable solution is obtained if the axial modes are neglected due to lack of the geometric stiffening effect, as previously mentioned [10,11]. In this study, the large transverse deformation of the robot arm is measured, and the measured experimental results are compared with the numerical results obtained using the FFR and ANCF models.…”
Section: Introductionmentioning
confidence: 96%
“…They found that unstable results were obtained with a two elements model. Motivated by their study, García-Vallejo et al [7,8] studied the instability of the ANCF models of the rotating beam. They found that there exists a critical value for the angular velocity of the beam that made unstable the models.…”
Section: Introductionmentioning
confidence: 99%